The Influence Of Creative Self-efficacy On Entrepreneurial Intention Through Creative Process Involvement And Attitude - Fauziah, Shani; Nugraha, Sukma; Mubarok, Teten Mohamad Sapril (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of creative self-efficacy on entrepreneurial intention in students of SMKN 10 Garut, with creative process involvement and attitude as mediating variables. Creative self-efficacy is believed to encourage individuals to engage in creative activities and have a positive attitude towards entrepreneurship. This study uses a quantitative approach with a path analysis method using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research sample was taken from SMKN 10 Garut students as many as 95 respondents. The findings of the test results show that creative self-efficacy affects entrepreneurial intention, self-efficacy affects creative process involvement, creative process involvement affects entrepreneurial intention, creative self-efficacy affects attitude, attitude affects entrepreneurial intention, creative self-efficacy affects entrepreneurial intention through creative process involvement, and creative self-efficacy affects entrepreneurial intention through attitude.